PENGARUH PENCEKOKAN EKSTRAK BIJI LUFFA ACUTANGULA, ROXB TERHADAP BERAT OVARIUM DAN BERAT BADAN MENCIT BETINA GALUR SWISS WEBSTER - Qomariah, Qomariah (E-Journal Widya Kesehatan dan Lingkungan, 2005)
This study was carried out to determine the effect to extract of Lufa acutangula, Roxb Extract (oyong) on infertility of female mice, Swiss Webster especially on reducing weight of ovarium and body weight. The treatment was given orally, which was divided in ten group consisting of two variables namely intervention dose of 5 groups (control/K; placebo/PLC, PI dose of 200 mg/kg bb; PII/dose of 300mg/kg bb and PIII/dose of 400mg/kg bb) and duration of intervention with two groups (20 days and 40 days). Result showed that the supplementation of oyong extract can reduce weight of ovarium but not the body weight of mice. The reduced ovarium weight was increased by supplementation of the extract with an effective dose of 200 mg/ kg body weight and 400 mg / kg body weight in 40 days of treatment.